Work- Family Conflict and Absenteeism in Selected Hotels in Abraka, Delta State, Nigeria - Ugo Chuks Okolie; Aghogho Victory Ighorhiohwunu (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
This study determined the effect of work-family conflict on workers absenteeism in selected hotels in Abraka, Delta State, Nigeria. A cross-sectional research design and convenience sampling technique were adopted. A questionnaire was employed as the research instrument for this study with 73 respondents deemed usable. Spillover theory was employed as the theoretical framework to guide the study. Data collected were analysed using descriptive and inferential statistics. The results of the study revealed that work-family conflict and burnout have positive significant influence on workers’ absenteeism, while work-family balance has no significant effect on workers’ absenteeism in selected hotels in Abraka, Delta State. Thus, the study recommends among others that managers of hotels in Abraka should develop and implement, family-friendly policies such as flexi-time, compressed work week and dependent care assistance in order to eliminate or reduced both involuntary and voluntary absenteeism among the workers.